Red Dawn - Hutcherson, Josh.; Peck, Josh, 1986-; Hemsworth, Chris; Metro-Goldwyn-Mayer.; Twentieth Century-Fox Film Corporation ([United States] : Metro Goldwyn Mayer, 2013)
The unsuspecting citizens of Spokane, Washington, wake up one morning to the shocking sight of foreign paratroopers dropping from the sky in a surprise attack on the United States. Soon the entire city's under enemy control, but a group of courageous teenagers has decided to fight back, waging an all-out war against the invaders, to take back their town and their freedom.
Keywords: Guerrillas -- Drama; Civil defense -- Drama; High school students -- Drama; Guerrillas -- Teatro -- Estados Unidos; Defensa civil -- Teatro -- Estados Unidos; Escuelas secundarias -- Teatro; Spokane (Wash.) -- Drama; Feature films; Fiction films; Action and adventure films; War films; Video recordings for the hearing impaired